How confident are medical students about making clinical decisions relying on the evidence? A cross-sectional questionnaire study - Frank, Luca; Hueber, Susann; van der Keylen, Piet; Roos, Marco (GMS Journal for Medical Education, 2019)
Objective: Giving information and providing advice on diagnostic tests is one of the tasks physicians must carry out personally. To do so, they must evaluate the evidence and integrate their findings into everyday practice. Clinical decisions should be based on evidence. How well current medical education prepares for such evidence-based clinical decision-making is largely unclear. Therefore, it was examined how confident medical students are in clinical decision-making based on evidence using epidemiological data. It was examined whether the decision-making confidence increases the higher the semester. Further questions were whether scientifically active medical students show higher decision-making confidence and whether the representation of figures as pictograms rather than tables positively influences the decision-making confidence. Methods: An online survey of the medical students of the Friedrich-Alex-ander-University Erlangen-Nürnberg was carried out. Respondents were presented with three clinical decision-making situations in random order for evaluation in the form of screening scenarios. In each case, the decision-making confidence also had to be specified. The scenarios contained only epidemiological data on existing screening tests. For each scenario, the numbers were presented as a table or a pictogram in a random fashion. In order to avoid false confidence resulting from preconceived opinions neither the illnesses nor the screening tests were mentioned by name. Results: Answers from 171 students were evaluated. Decision-making confidence in dealing with the numbers does not increase in higher semesters (rPearson =0.018, p=0.41). Scientific work is not associated with a higher decision-making confidence (t(169)=-1.26, p=0.11, d=-0.19). Presentation as a pictogram leads to a higher decision-making confidence compared to tables (Pictogram: M=2.33, SD=1.07, Table with numbers: M=2.64, SD=1.11, t(511)=3.21, p<0.01, d=0.28). Conclusions: Medical students from higher semesters show no higher decision-making confidence compared to medical students from lower semesters. Curricular events and scientific work, such as a doctoral thesis, do not seem to strengthen the required skills sufficiently. If evidence is presented in the form of pictograms, this seems to improve student confidence in decision-making.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Clinical decision-making; Doctoral thesis; Evidence-based medicine; Medical students; Pictogram; Uncertainty